Malnutrition post liver transplant - Glombicki, Alan (Indonesian Nutrition Association, 2024)
Before undergoing liver transplantation, it is essential for patients to maintain optimal nutrition. Malnutrition is common among individuals with liver disease and can have detrimental effects on the outcome of the surgery. Research has shown that malnourished patients are at higher risk of developing postoperative complications, such as infections, poor wound healing, and longer hospital stays.